توظيف اللعب في إكساب وتطوير المهارات الحركية الأساسية لدي تلاميذ المرحلة الابتدائية في ضل غياب معلم متخصص - هداج, حمزة; رواب, عمار (جامعة الوادي - University of Eloued, 2021)
يعد اللعب نشاطا مهما في حياة الطفل، باعتبار اللعب وسيط تربوي مهما ومدخل أساسي، في إطار العملية البيداغوجية تقول الدكتورة سوزانا ميلر أخصائية علم نفس الطفل لقد ظلت كلمة "لعب" زمنا طويلا تعبيرا يشبه سلة المهملات اللغوية التي نلقي فيها بكل سلوك اختياري ، و لكن لا يبدو له أي استعمال واضح من الناحية البيولوجية أو الاجتماعية أو التربوية وبالرجوع إلى زمن أفلاطون و أرسطو, حيث نادى الأول في كتابه " القوانين" بتوزيع تفاحات على الأطفال لمساعدتهم على تعلم الحساب، و منح أدوات بناء مصغرة لمن يتوقع أن يكونوا بنائين في المستقبل، بينما دعا الثاني إلى تشجيع الأطفال على اللعب بما سيكون عليهم أن يفعلوه بشكل جدي حين يصيروا راشدين ونظرا لأهميته هدفت هذه الورقة العلمية ،إلي تبيان اللعب بوصفه طريقة تعلميه تعليمية، من اجل إكساب أطفال المرحلة الابتدائية المهارات الحركية الأساسية ، وكذا تطويرها في ضل غياب معلم متخصص ،وهذا من خلال توظيف جميع أشكال اللعب، من العاب حركية والعاب صغيرة ،وكذا القصة الحركية، مع تلاميذ المرحلة الابتدائية، لملائمتها لسنهم وخصائص تعلمهم الحركي لمهارات المشي- الجري –الرمي – الوثب- الركل – الحجل-اللقف. : Playing is perceived to be an important activity in child’s life. Besides, it is considered as a significant educational channel and primary principles in pedagogical process. The child Psychologist Dr. Suzanna Miller says for a long time has been a expression as a language waste basket in which we put every optional behavior ,but it does not seem to have any clear use in term of Biological , Social or Pedagogical by returning to the time of Plato and Aristotle where the first called in his book ‘Laws’ for distributing apples to the children to help them learn arithmetic, and to give them a small building tools to those expect to be builders in the future, while the second called for encouraging children play what they would have to do seriously when they became adults . Regarding to its importance, in this research we aim to prove the playing as a tool for learning and interaction; For the purpose of training children of primary school to acquire and develop general skills of physical activity. All this, through using different forms of physical exercise and small playing, at primary school because it is quit suitable to their age and abilities to acquire the following physical exercise skills: walking, running, throwing, jumping, kicking, and capturing.
The role of playing in acquiring and enhancing generalskills of physical activity at primary school
مقال بمجلة السراج في التربية وقضايا المجتمع . مج 05 ع01. فيفري 2021 . جامعة الوادي
Keywords: اللعب –المهارات الحركية الأساسية- تلاميذ المرحلة الابتدائية: Playing, general skills of physical activity, primary school